Medicinal Water? The occurrence and fate of pharmaceuticals in aquatic environments A short communication - Sánchez-Murillo, Ricardo (Uniciencia, 2012)
Although very little is known about the transport, fate and toxic effects of medical compounds in aquatic environments, the presence of these compounds in potable water sources can no longer be overlooked. We can argue that trace concentrations of drugs in the water is relatively a minor problem, however, the current and future demands on global potable freshwater supplies will probably lead to greater incidents of indirect and direct water-reuse situations at the local, regional, and cross-border levels. It is important to remark that the solution of this emerging ecological issue does not rely on new and better wastewater treatment technologies, but a new paradigm of responsibility and the understanding of the relations between anthropogenic actions and their ecological effects as well. The objective of this brief communication is to present the state of the art of research conducted in the last decade in Europe and United States concerning the presence of pharmaceuticals products in aquatic environments.